2022
DOI: 10.24304/kjcp.2022.32.2.84
|View full text |Cite
|
Sign up to set email alerts
|

General Public Knowledge Regarding Topical Corticosteroids: A Nationwide Survey in South Korea

Abstract: Topical corticosteroids (TCs) are widely used for various skin conditions. Although safe when used appropriately, misuse and abuse of TCs could result in local and systemic side effects. [1][2][3] Reports of misuse and abuse resulting in serious adverse outcomes have been reported in India 4-7) and Africa 8) owing to the high availability of over-the-counter (OTC) TCs. 7,8) In South Korea, TCs with various potencies are available without a prescription. Additionally, there is an increasing global trend of self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
3
5
0
Order By: Relevance
“…The awareness and knowledge of corticosteroids have been evaluated in numerous prior studies [26][27][28]. Aligning with our research findings, a nationwide survey conducted in South Korea identified a notable prevalence of incorrect responses related to the application methods and indications of corticosteroids in certain aspects.…”
Section: Discussionsupporting
confidence: 80%
“…The awareness and knowledge of corticosteroids have been evaluated in numerous prior studies [26][27][28]. Aligning with our research findings, a nationwide survey conducted in South Korea identified a notable prevalence of incorrect responses related to the application methods and indications of corticosteroids in certain aspects.…”
Section: Discussionsupporting
confidence: 80%
“…17 Similarly, Seo et al reported that among 3000 participants surveyed, only 2% were aware of the potential systemic side effects of TCs use. 27 By comparison, 15.5% of the participants in our study were aware of the potential systemic side effects of TCs use. Hence, providing information on the potential systemic side effects of TCs is crucial in order to ensure public safety with regard to TCs use.…”
Section: Discussionmentioning
confidence: 73%
“…Hence, providing information on the potential systemic side effects of TCs is crucial in order to ensure public safety with regard to TCs use. 27 …”
Section: Discussionmentioning
confidence: 99%
“…This lack of understanding is reflected in both local and international studies; a nationwide South Korean study revealed that over half of the participants were unaware of the side effects of topical corticosteroids, and 1% believed there were none. One-fourth of the participants agreed that topical corticosteroids should be used until symptoms resolve, irrespective of the duration [10]. Similarly, a Saudi cross-sectional study found that 61.3% of its participants were unaware of the side effects resulting from the misuse of topical corticosteroids on the face [11].…”
Section: Discussionmentioning
confidence: 99%